The challenges of lack of sustainability of cooperatives : a perspective of selected art and craft cooperatives of Muyexe Village in Greater Giyani Municipality of Limpopo Province in South Africa - Mabunda, Queen (My University, 2017)
Cooperatives play a significant role in the country’s economic growth, job creation and poverty reduction. Hence, the number of registered cooperatives in South Africa has been growing very fast. However, the main challenge is that the majority of these cooperatives are underperforming. The apartheid legacy has caused many of these cooperatives to be poorly developed or unsustainable. The aim of this study was to investigate the challenges of lack of sustainability of art and craft cooperatives in Muyexe village of Mopani district in Limpopo Province. For this purpose, eight art and craft cooperatives were used as a survey. The study used mixed research methods to collect both qualitative and quantitave data. Data was gathered from eight (8) art and craft cooperatives in Muyexe village. The cooperatives where data was collected are Progress, Tsakane, Rirhandzu, Hitekani, Vutivi, Tiyimeleni, Vuyeriwani and Pfuka Muyexe art and craft cooperatives. . Data collection was done through structured questionnaires and interviews. Secondary data was gathered through extensive literature review. The population of the study is eight art and craft cooperatives comprised of 88 members. 60 respondents represented all the eight cooperatives. Two groups of respondents participated in this study. The first group was composed of cooperatives members (n=50) and the second group of respondents were the cooperatives board of directors (n=10). The findings revealed some of the factors that cause unsustainability of cooperatives in the area of the study. These factors are lack of good corporate governance practices, inadequate developmental programmes, lack of experience in managing cooperatives, lack of coflict management, lack of ownership and others. To enhance the sustainability of cooperatives the research recommends that the policy makers and agencies should be encouraged to develop enough developmental programmes that will enhance the sustainability of cooperatives in the area of the study.
Thesis (M. Dev.) -- University of Limpopo, 2017.
Keywords: Cooperatives; Economic growth; Poverty reduction; Job creation; Cooperative societies; Sustainable development